Which numbers are real? - Henle, Michael (Washington : Mathematical Association of America, 2012)
An exploration of number systems that extend and generalise the real numbers, of interest to students, mathematics teachers and enthusiasts
1. Axioms for the reals -- 2. Construction of the reals -- 3. The complex numbers -- 4. The quaternions -- 5. The constructive reals -- 6. The hyperreals -- 7. The surreals
Includes bibliographical references (p. 205-208) and index
Keywords: Number theory; Numbers, Complex; Numbers, Real